Analisa Penerapan Jual Beli Pesanan Pada Rubber Part di PT. Banshu Rubber Indonesia - Ismarudi; Riski Siti Nurjanah; Siti Hapipah; Ahmad Saepudin (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2022)
The background that became the object of the researcher was PT. Banshu Rubber Indonesia conducts buying and selling with an order system that is carried out with the provisions of the terms, pillars and rules that form the basis for the sale and purchase, so that researchers conduct research to analyze the application of buying and selling Rubber Parts at PT. Banshu Rubber Indonesia. The purpose of this study was to determine the application of the order system to the sale and purchase of Rubber Parts at PT. Banshu Rubber Indonesia, and to find out the implementation of buying and selling Rubber Part Orders at PT. Banshu Rubber Indonesia in the perspective of Sharia Economics. This research is a qualitative type using descriptive method. The results of this study indicate that the implementation of transactions, ordering processes or orders for goods by PT Bansu is carried out by the Purchase department which directly places orders to suppliers. The info includes material specifications, sizes, quantity and quality standards. The customer service then issues a PO (Purchase Order) for the order including the delivery date, payment method, delivery date, and return method if Not Good products are found. Furthermore, the delivery process is carried out by PT. Banshu Rubber Indonesia based on the delivery schedule that has been made in the PO. The consignee checks the goods before making a receipt. The check includes the number of goods, the visual condition of the goods and the suitability of the goods with the notes listed on the delivery letter. Next is the payment system of PT. Banshu Rubber Indonesia with suppliers explained that every buying and selling transaction of paying rubber parts is carried out using an invoicing system where payment will be made 30 days after the invoice is received. Sharia Perspective Review, Practice Analysis of the Application of Istishna Contracts in the Sale and Purchase of Rubber Parts at PT. Banshu Rubber Indonesia has implemented the concepts of the Istishna contract, it appears that the conditions for each pillar have been fulfilled, such as the pillars of the parties to the contract, the object ordered, the payment system in the order, and sighat or consent qobul.